Maryland Prepares to be Abortion Safe Haven - Dasgupta, Sunil; Kelly, Ariana (I Hate Politics Podcast, 2022)
With 26 US states set to impose degrees of abortion bans following the Supreme Court’s reversal of Roe v Wade, Maryland is likely to become the southern-most state on the Eastern seaboard to offer fully legal abortions and the state’s providers are expecting women from abortion-banned states to travel to Maryland for services. Sunil Dasgupta talks with Maryland Delegate Ariana Kelly about how the state is preparing. Kelly has been one of the leading voices pushing to expand reproductive health services for Marylanders and out-of-state patients. Music by Rockville-based rock and roll band, The Treading Lemmings.
Keywords: I Hate Politics